2010
DOI: 10.1111/j.1532-5415.2010.02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fear of Falling and Outcomes of an Inpatient Geriatric Rehabilitation Population—Fear of the Fear of Falling

Abstract: OBJECTIVES:To examine the effects of various risk factors on three functional outcomes during rehabilitation. SETTING: Geriatric inpatient rehabilitation unit. DESIGN: Observational longitudinal study. PARTICIPANTS: One hundred sixty-one geriatric rehabilitation inpatients (men, women), mean age 82, who were capable of walking at baseline. MEASUREMENTS: Functional status was assessed weekly between admission and discharge and at a followup 4 months later at home using the function component of the Short FormFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…In addition, while the participants in our study were comparable to participants in other studies with respect to gender and type of fracture (7,12,25), FoF was assessed in vulnerable patients with hip fractures of very high age and with a high number of comorbidities. In particular, this group is in need of multidisciplinary rehabilitation (44) and at risk of FoF (16).…”
Section: Regression Analysis and Modelmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, while the participants in our study were comparable to participants in other studies with respect to gender and type of fracture (7,12,25), FoF was assessed in vulnerable patients with hip fractures of very high age and with a high number of comorbidities. In particular, this group is in need of multidisciplinary rehabilitation (44) and at risk of FoF (16).…”
Section: Regression Analysis and Modelmentioning
confidence: 66%
“…It is widely used and regarded as a suitable instrument for FoF (24). the impact of FoF is best illustrated by its role in predicting rehabilitation outcomes at discharge and follow-up (25). Reduction in FoF may therefore improve the outcomes of rehabilitation after a hip fracture.…”
mentioning
confidence: 99%
“…This could represent an important finding if patients changed behavior due to difference in fear of falling. Earlier studies have shown a strong correlation between FESI score and physical function in geriatric populations, (327) and it is likely that there is a similar relationship for FESI-s. On the other hand both CGC and OC had scores of FESI-s in the same level (9-13) indicating moderate risk of falling in both groups and therefore some degree of uncertainty of the clinical impact of our results. (289) FESI-s is sensitive in patients with low function, while it has a ceiling effect in high-function patients.…”
Section: Othermentioning
confidence: 88%
“…Literature states that exposure to FoF contributes to a loss of independence or disability through the restriction of activities [21,22] since it is associated with an increased risk of functional decline [23], reduced physical activity, lower perceived physical health status, lower quality of life and increased institutionalization [24]. Despites being more frequent among fallers, FoF and activity restriction are not exclusive of these persons.…”
Section: Fear Of Fallingmentioning
confidence: 99%